2019
DOI: 10.3390/ijerph16122081
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review Mapping Research on Green Space and Associated Mental Health Benefits

Abstract: Background: There is a growing interest in research investigating the association between green space (GS) and mental health and wellbeing (HWB), in order to understand the underlying mechanisms. Accordingly, there is a need to map the literature and create an overview of the research. Methods: A scoping review approach was used to map literature on GS, including context and co-exposures (the GS exposome), and their associations with mental HWB. The review considers mental HWB definitions and measurements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 350 publications
7
81
0
Order By: Relevance
“…With respect to mental health, most studies on the effects of greenspace on mental health use self-reported measures 14 , 26 with high variability in the number of different measures used 26 . This variability of measures used to assess mental health make comparability, and aggregating evidence on the effects of urban greenspace on mental health, difficult 26 . There is a need for more objective indices of mental health 14 .…”
Section: Introductionmentioning
confidence: 99%
“…With respect to mental health, most studies on the effects of greenspace on mental health use self-reported measures 14 , 26 with high variability in the number of different measures used 26 . This variability of measures used to assess mental health make comparability, and aggregating evidence on the effects of urban greenspace on mental health, difficult 26 . There is a need for more objective indices of mental health 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Research across a wide spectrum of disciplines has empirically explored the linkages between nature or ecosystems and human well‐being with the conclusion that nature generally makes people happier and healthier (both physically and mentally; see e.g. Annerstedt & Währborg, ; Hartig, Mitchell, de Vries, & Frumkin, ; Russell et al, ; van den Bosch & Ode Sang, ; Wendelboe‐Nelson, Kelly, Kennedy, & Cherrie, ; White et al, ). Recently, the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services (IPBES) Regional Assessment for Europe and Central Asia revealed the dynamic relationships between nature's contributions to people, biodiversity and ecosystems, and their relevance for human well‐being (respectively quality of life in their terminology; Martín‐López et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of prior studies have compared nature and urban experiences and the near universal finding among these studies is that natural green environments promote health and well-being (Choudhry et al, 2015;Hartig et al, 2014;Sandifer, Sutton-Grier & Ward, 2015;Wendelboe-Nelson, Kennedy & Cherrie, 2019). This near-universal finding supports that natural environments are generally enjoyed more than urban ones.…”
Section: Notesmentioning
confidence: 72%